Analisis Pemanfaatan Jerami Padi Sebagai Bahan Bakar Pembangkit Listrik Tenaga Biogas - Ananda, Risky; Miefthawati, Nanda Putri (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
This research was conducted in Limbukan Village, with a rice field area of 1,171 ha producing 5,855 tons of straw. The straw is currently not utilized, so it can potentially cause environmental pollution. The Limbukan area depends on electricity from PLN. In the face of the challenges of increasing energy demand, fluctuating energy prices and the negative environmental impact of unused straw waste, renewable energy assessment has become crucial for identifying sustainable alternatives. To overcome this problem, this research focuses on the potential of rice straw waste as a renewable energy source, with an emphasis on biogas fuel production. This research method involves the use of anaerobic fermentation to calculate biogas potential using Superpro Designer simulation. The research results show that rice straw waste has the potential to produce 208,393 m³ of biogas per day. Apart from that, by utilizing biogas fuel, this study also calculated the potential for electrical energy of 1,271,197.3 kWh. By using a 400 KW generator set, 1,200 Watts of electrical energy can be distributed to 333 residents' homes for approximately 24 hours. This research provides an overview of the potential for utilizing rice straw waste as a renewable energy source, especially in the context of biogas and electrical energy production. It is hoped that these findings can become a basis for developing sustainable solutions for managing agricultural waste and providing energy for local communities.Keywords - Anaerobic Digestion, Biogas, Rice Straw.